Analytical finite-Lamor-radius and finite-orbit-width model for the LIGKA code and its application to KGAM and shear Alfvén physics. (November 2018) - Lauber, Ph.; Lu, Z.
Abstract: In this paper, a finite Larmor radius (FLR) and finite orbit width (FOW) model within the LIGKA [1] framework is derived and its implementation in LIGKA is verified against analytical theory. The model is based on an expansion in k ⊥ ϱi and thus valid for low and intermediate mode numbers. Assuming Maxwellian distribution functions and considering circulating ions only, analytical expressions for the non-adiabatic response in the quasi-neutrality (QN) and the gyrokinetic moment equation (GKM) are derived. It is shown how these expressions, also valid for n ≠ 0 can be connected to results in the literature for n = 0. Verification tests with analytical literature [2] are carried out for mode frequency, damping and radial mode propagation. A set of parameters is chosen that is based on recent experiments at ASDEX Upgrade [3] featuring strong EGAM (energetic particle induced geodesic acoustic mode) and BAE (beta-induced Alfvén eigenmode) activity. For finite n, the model can be used to determine the local radiative damping consistently, which is needed for the fast evaluation of linear AE (Alfvén eigenmode) stability boundaries that are typically required by energetic particle transport models.